2017
DOI: 10.1103/physrevlett.119.184802
|View full text |Cite
|
Sign up to set email alerts
|

Passive Linearization of the Magnetic Bunch Compression Using Self-Induced Fields

Abstract: International audienceIn linac-driven free-electron lasers, colliders, and energy recovery linacs, a common way to compress the electron bunch to kiloampere level is based upon the implementation of a magnetic dispersive element that converts particle energy deviation into a path-length difference. Nonlinearities of such a process are usually compensated by enabling a high harmonic rf structure properly tuned in amplitude and phase. This approach is however not straightforward, e.g., in C-band and X-band linac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…A dechirper system [56,57] was installed 120 m upstream of the entrance of the undulator line to control the electron bunch time-energy longitudinal distribution. Longitudinal phase space control with a dedicated wakefield device had been also previously demonstrated at other facilities [58][59][60][61][62]. The system is composed by two 2-m long modules, one vertical and one horizontal.…”
mentioning
confidence: 99%
“…A dechirper system [56,57] was installed 120 m upstream of the entrance of the undulator line to control the electron bunch time-energy longitudinal distribution. Longitudinal phase space control with a dedicated wakefield device had been also previously demonstrated at other facilities [58][59][60][61][62]. The system is composed by two 2-m long modules, one vertical and one horizontal.…”
mentioning
confidence: 99%
“…The favored solution to resolve the nonlinearity is to use a high frequency passive corrugated structure [47], to correct the second order curvature prior to compression [48,49]. When a high current electron beam goes through a corrugated structure, the resulting wakefield can be used to modify the longitudinal phase distribution of the beam [50].…”
Section: Time-dependent Simulations and Longitudinal Phase Space Matc...mentioning
confidence: 99%
“…Finally at FERMI it has been recently demonstrated that wakefields can also be used to achieve passive linearization of the longitudinal phase space in combination with magnetic bunch compression [48].…”
Section: Non Linearity In the Longitudinal Phase Space Distributionmentioning
confidence: 99%